Teknologi Biopori sebagai Solusi Pengelolaan Sampah Organik Rumah Tangga di Desa Linggoasri - Rizki Nor Amelia; Nyar Osmi Arianti; Yuliana Titi Rachmasari (Jurnal Pengabdian Masyarakat Satya Widyakarya, 2026)
The issue of food waste in Linggoasri Village remains high due to the lack of an adequate management system, which has the potential to cause environmental disturbances. This community service activity aims to introduce and implement Biopori technology as a solution to reduce organic waste accumulation and produce useful compost. The methods used included observation, lectures, discussions, and hands-on practice in making Biopori with the involvement of the Women Farmers Group. The results of the activity demonstrated an increase in the community's understanding of the function of Biopori and the construction of Biopori holes, which serve as a means of water absorption, organic waste decomposition, and compost production. The application of Biopori has proven effective as a simple and practical technology in addressing household organic waste issues. Moving forward, the community is expected to routinely manage organic waste through Biopori to ensure its benefits are sustainable